The Influence of Content Marketing, Influencer Marketing, and Live Streaming on General Z Fashion Product Purchase Decisions on Tiktok Shop - Nurul Aeni; Lalu Edy Herman Mulyono (LP2M IAIN Palopo, 2026)
This study aims to analyze the simultaneous and partial effects of Content Marketing, Influencer Marketing, and Live Streaming on the purchasing decisions of Generation Z (Gen Z) consumers for fashion products on TikTok Shop. Generation Z is recognized as a group that is highly connected to social media and quick to adapt to trends, making TikTok Shop a relevant platform for fashion product marketing. The research employed a quantitative method with a survey approach, involving Gen Z respondents who actively use TikTok Shop to purchase fashion products. The sampling technique used was purposive sampling, with a total sample of 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that Content Marketing, which focuses on engaging, creative, and informative content, has a positive and significant effect on Gen Z purchasing decisions. Similarly, Influencer Marketing, through recommendations and the credibility of followed influencers, shows a positive and significant impact. In addition, the Live Streaming feature on TikTok Shop, which offers real-time interaction, product demonstrations, and exclusive promotions, also has a significant influence in encouraging purchases. Simultaneously, these three variables contribute substantially to explaining the variation in Gen Z fashion product purchasing decisions on TikTok Shop. The practical implication of this study is to provide insights for fashion businesses to optimize their digital marketing strategies on TikTok Shop, particularly by leveraging content features, influencer collaborations, and live streaming sessions to increase sales and effectively reach the Gen Z market segment.